KAJIAN EKONOMI POLITIK MEDIA : (Hiperealitas Ruang Politik Publik) - Kamaruddin Hasan (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
This study aimed at enhancing a comprehension about economic and political power, media and public spaces. It included an effort to synchronize the relation of social media, market public and power or nation. Furthermore, the parties who have authorities in economic and politics are the media owners which involved in political practice and tend to ignore public interest. Media industries controlled by some global and national corporations which dominate the public are used for political-economy pragmatism. This study used qualitative research related to critical paradigms in perspective of political-economy media theory in which the theory chosen is Professor Vincent Moscow theory. The data was gained by means of observation, interview, and document through validity of media and public. It includes focus group discussion held with weekly review of Atjeh Analyst Club (A2C) and Sekolah Menulis dan Kajian Media (SMKM-Atjeh). The result of the study shows that the media has heavily involved in oligarchy politic, monopoly and hegemony so that the public opinion is on the edge. The content forms of media are more selected by political power, economy, capitals owner and media income orientation rather than the public although the public has the right to select the truth and correct information. It is expected that the study provides the benefit to raise the public’s critical awareness, the regulation and policy which is oriented to the public so that the media becomes truly public right and this study is expected to enrich previous practical and theoretical findings.